REGISTER PETANI SAWIT DI DESA SUMBER AGUNG KECAMATAN BATU AMPAR KABUPATEN KUBU RAYA - Warsul Ulamaut Tamami; Ahmad Rabi’ul Muzammil; Agus Syahrani (Universitas Tanjungpura, 2021)
AbstractRegister is a variation of language that involves the language being used for certain fields or purposes. The reason the researcher chose the title of the study of the Palm Oil Farmer Register in Sumber Agung Village, Batu Ampar District, Kubu Raya Regency was to inventory the registers used by oil palm farmers in Sumber Agung Village. The general problem in this study is the form of registers, types of registers, and registers that experience changes in meaning. This research method is descriptive and the form of this research is qualitative research. Sources of data in this study were oil palm farmers in Sumber Agung Village and data collection techniques in this study were tapping and interview techniques. Based on the results of data analysis, there are 52 registers used by oil palm farmers in Sumber Agung Village. Of the 52 registers, 21 are closed registers and 31 are open registers. In addition, of the 52 registers found, there are several registers that have undergone a change in meaning caused by the environment, a combination of words, and associations. Suggestions for future researchers is that this study can be used as input to obtain optimal research results.Keywords: Register, Oil Palm Farmers